Assessment of consolidation behavior of golden horn marine dredged material - Berilgen, SA; Berilgen, MM; Özaydin, KI; Biçer, P (TAYLOR & FRANCIS INC, 2006)
Polluted sea bottom sediments from Golden Horn in Istanbul have been dredged and stored on land at a disposal site. Reclamation of the disposal site was highly dependent on prediction of self-weight consolidation behavior of the dredged material, which is analyzed numerically using software which employs a nonlinear finite strain solution algorithm ( Fox and Berles 1997). The material parameters needed for the numerical model are determined using a seepage-induced consolidation testing system and prediction of the numerical model is tested against experimental observations in a slurry consolidation model tank. The numerical modeling of the field behavior at the disposal site could be successfully accomplished using sediment property data from the seepage-induced consolidation test.
Keywords: consolidation; compressibility; contaminated soils; geotechnical parameters; numerical analysis; PERMEABILITY; Engineering; Oceanography; Mining & Mineral Processing